Optical polarization observations in the Scorpius region: NGC 6124 - Vergne, María Marcela (2010)
We have obtained optical multicolour (UBVRI) linear polarimetric data for 46 of the brightest stars in the area of the open cluster NGC 6124 in order to investigate the properties of the interstellar medium (ISM) that lies along the line of sight towards the cluster. Our data yield a mean polarization efficiency of PV/E(B - V) = 3.1 ± 0.62, i.e. a value lower than the polarization produced by the ISM with normal efficiency for an average colour excess of E(B - V) = 0.80 as that found for NGC 6124. Besides, the polarization shows an orientation of which is not parallel to the Galactic disc, an effect that we think may be caused by the Lupus cloud. Our analysis also indicates that the observed visual extinction in NGC 6124 is caused by the presence of three different absorption sheets located between the Sun and NGC 6124. The values of the internal dispersion of the polarization (ΔPV ∼ 1.3 per cent) and of the colour excess (ΔE(B - V) ∼ 0.29 mag) for the members of NGC 6124 seem to be compatible with the presence of an intracluster dust component. Only six stars exhibit some evidence of intrinsic polarization. Our work also shows that polarimetry provides an excellent tool to distinguish between member and non-member stars of a cluster.